The Influence of Overweight and Obesity on Treatment Response in Juvenile Idiopathic Arthritis - Giani, Teresa; De Masi, Salvatore; Maccora, Ilaria; Tirelli, Francesca; Simonini, Gabriele; Falconi, Martina; Cimaz, Rolando (Frontiers in Pharmacology, 2019)
Background: There is evidence that obesity could be a risk factor for the severity and response to treatment in adult patients with RA due both to the mechanical effect of overweight and to the potential pro-inflammatory effects of cytokines produced by adipose tissue. Objectives: To evaluate the role of overweight and obesity in a cohort of young patients with Juvenile Idiopathic Arthritis (JIA) in terms of incidence, disease activity, outcome and response to treatments. Methods: This single-center retrospective cohort study evaluated 110 children affected by JIA under treatment with conventional disease modifying antirheumatic drugs (DMARDs) and biologic agents. Changes from baseline in ESR, CRP, number of active joints, and BMI were analyzed under each treatment until last visit. Body mass index (BMI) categories of 5-84th (normal weight), 85-94th (overweight), and ≥95th (obese) percentile were used. Patients with systemic JIA, uveitis, chronic comorbidities, or under other potentially confounding systemic treatments were excluded. Uni- and multivariate analyses were performed. Results: One hundred and ten JIA patients (polyarticular n=50, oligoarticular n=38, psoriatic n=12, enthesitis-related arthritis n=8, undifferentiated n=2) were enrolled in the study, 75% girls, 25% boys. The mean age at treatment onset was 6.09 years. Baseline BMI was ≤ 84th percentile in 80 patients, 85-94th in 27, and ≥ 95th in 3. We did not observe a significant association between BMI and ESR, CRP, or number of active joints at baseline, while involvement of the joints of lower limbs was significantly greater (p=0.025) in overweight/obese patients. However a trend toward lower remission rates and higher number of relapses, both after DMARDs and biologics, in patients with higher BMI were observed. Conclusion: This study focuses on the relationship between overweight/obesity and JIA. A significant correlation between obesity and a greater involvement of the joints of the lower limbs at baseline was demonstrated. Furthermore our data suggest that obesity could negatively influence the course of the disease as well as treatment response.